MARINE TOURISM MARKETING STRATEGY THOUSAND ISLANDS - Feliza Adly, Ananda Princess; Priyanto, Priyanto (UI Scholars Hub, 2019)
This task of the final work consists of analysis of Indonesia tourism marketing process for the Thousand Islands, started from the planning step up till the actuating step. In this task of final work IS ALSO Described the obstacles in the tourism marketing process has been done and roomates Also describes the right steps of tourism marketing to increase of the number of tourist. This task of the final work is arranged by counting the data analysis. The result of analysis shows that Indonesia tourism marketing for the Thousand Islands has not been done well cause of the lackness of tourism human resources.